Chemical and nutraceutical properties of Coreopsis tinctoria. (March 2015) - Guo, Limin; Zhang, Wensheng; Li, Shiming; Ho, Chi-Tang
Highlights: This is the first comprehensive review of Coreopsis tinctoria ( C. tinctoria ). Dominant flavonoids in C. tinctoria are thoroughly reviewed for the first time. Updated study results of the biological properties of C. tinctoria are summarized. This review will be an important reference for future research on C. tinctoria. Abstract: A Chrysanthemum family member, Coreopsis tinctoria has been grown in high plateau regions, particularly in Xinjiang, China, for many decades. It has been reported that Coreopsis tinctoria ( C. tinctoria ) possesses many biological activities, including hypoglycaemic activity, hypolipidaemia activity, blood pressure reduction activity, and antioxidant activity. Previous reviews of C. tinctoria have mostly focused on one of its characteristics, such as analytical or separation chemistry of its major components, or biological properties of its extract, or phytotaxonomy, among others. The aims of the present review are to introduce the analysis and isolation of identified phytochemicals in C. tinctoria and the biological properties of C. tinctoria extracts with targeted indication of nutraceutical properties, and to endeavour to develop a relationship between the chemical identity and pharmacological effects of C. tinctoria .